2018
DOI: 10.1101/351015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Xist IncRNA forms silencing granules that induce heterochromatin formation and repressive complexes recruitment by phase separation

Abstract: order chromatin structure, Polycomb Repressive Complexes 1/2 (PRC1/2), nuclear matrix, RNAprotein interaction, RNA secondary structure, ribonucleoprotein (RBN). Main textLong non-coding RNAs (lncRNAs) are RNA molecules longer than 200 bases that lack coding potential 1,2 . They represent a significant portion of the cell transcriptome 3 and work as activators or repressors of gene transcription acting on different regulatory mechanisms 4-6 . Indeed, lncRNAs can act as macro-scaffolds for protein recruitment 7-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
(55 reference statements)
1
2
0
Order By: Relevance
“…Multivalent interactions underlie phase separation, a general mechanism of organization in cells. Recently it was reported that the XIST RNP complex forms a distinct liquid phase in cells, probably due to the repetitive sequences in XIST and the intrinsically disordered regions in XIST-associated proteins (Cerase et al, 2018). Our analysis showed that XIST associated proteins bind XIST in clustered patterns, supporting the multivalent interactions.…”
Section: A Comprehensive Structure-interaction Model Of the Xist Rnp supporting
confidence: 73%
“…Multivalent interactions underlie phase separation, a general mechanism of organization in cells. Recently it was reported that the XIST RNP complex forms a distinct liquid phase in cells, probably due to the repetitive sequences in XIST and the intrinsically disordered regions in XIST-associated proteins (Cerase et al, 2018). Our analysis showed that XIST associated proteins bind XIST in clustered patterns, supporting the multivalent interactions.…”
Section: A Comprehensive Structure-interaction Model Of the Xist Rnp supporting
confidence: 73%
“…Xist will cause the X chromosome in its place to relocate to the outer edge of the nucleus. Afterwards, it interacts with PRC2 to elevate H3K27me3, resulting in X chromosome silencing and heterochromatinization [18,19] (3) HOTTIP recruits WDR5 to the promoter region of HOXA, the critical developmental gene, to activate its expression [20,21]. In addition, lncRNAs can block transcription factors from binding to the target region (Figure 2c).…”
Section: Long Non-coding Rna Functionsmentioning
confidence: 99%
“…Finally, it has been recently hypothesized that XIST might silence the X chromosomes by forming phase-separated "silence granules", due to its interactions with disordered proteins, including FUS and hnRNPA2 [22,153]. Although experimental evidence is required to support this suggestion, it provides an interesting new perspective on the biochemistry of XIST-mediated silencing.…”
Section: Organizers Of Phase Separationmentioning
confidence: 99%